Service Members Prefer a Psychotherapist Who Is a Veteran - Johnson, Travon S.; Ganz, Alexis; Berger, Stephen; Ganguly, Anindita; Koritzky, Gilly (Frontiers in Psychology, 2018)
The military is experiencing high rates of mental illness, yet service members and veterans with mental health problems often choose not to seek treatment. Based on clinical-psychology models of client-therapist matching and cultural competency, we hypothesized that willingness to seek treatment among military personnel is higher when the potential psychotherapist is a discharged veteran. Seventy-seven military personnel (73% men, 70% White, Mage=34.2) took part in the study. As hypothesized, the majority of participants indicated that they would prefer to see a psychologist who is a veteran. When responding to vignettes, ratings of the psychotherapist’s ability to understand the client (a soldier post-deployment), of his ability to help such a client, and of whether the client should seek treatment from this psychotherapist were higher when the psychotherapist was a veteran compared to when he had no military experience. There were no between-group differences in age, years of service, deployment history, or attitudes toward psychotherapy in general. Similarly, gender and education level had no effect on the results. These findings imply that having the opportunity to receive treatment by a psychotherapist who is a veteran may remove barriers for treatment and encourage more service members and veterans to seek and obtain the help that they need. This can be done by communicating these findings to the military population and by encouraging therapists who have military experience to make this fact known to their potential clients.